2022
DOI: 10.58466/jap.v1i2.762
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pemberian Biochar Tandan Kosong Kelapa Sawit Terhadap Pertumbuhan Stek Lada Pada Lapisan Tanah Subsoil Ultisol

Abstract: Biochar tandan kosong kelapa sawit (TKKS) berpotensi untuk meningkatkan ketersediaan unsur hara yang dibutuhkan tanaman yaitu N, P, K, Ca dan Mg, yang bertujuan untuk meningkatkan pertumbuhan pada stek lada (Piper nigrum L) dengan media lapisan tanah subsoil ultisol. Penelitian ini bertujuan untuk mengetahui komposisi terbaik biochar tandan kosong kelapa sawit untuk pertumbuhan stek lada. Penelitian ini telah dilaksanakan mulai Mei sampai Agustus 2022 di Jl. Brigjen Katamso No.02, Sukaharja Kecamatan Delta Paw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…It is the optimum dose in providing habitat for microorganisms in the soil, which is closely related to the availability of nutrients, texture, and moisture. It supports the root system [31]. A high root dry weight value indicates that root formation is very good.…”
Section: The Wet Weight and Dry Weight Of Rootsupporting
confidence: 56%
See 1 more Smart Citation
“…It is the optimum dose in providing habitat for microorganisms in the soil, which is closely related to the availability of nutrients, texture, and moisture. It supports the root system [31]. A high root dry weight value indicates that root formation is very good.…”
Section: The Wet Weight and Dry Weight Of Rootsupporting
confidence: 56%
“…The treatments were (A) 100% soil (control), (B) 5% EFB biochar, (C) 10% EFB biochar, and (D) 15% EFB biochar. Previous research [31] showed that the optimal EFB biochar composition was 15%. After four months of weaning, the plants were dismantled to observe the root growth parameters, i.e., root length, root volume, root wet weight, and root dry weight.…”
Section: Methodsmentioning
confidence: 99%